ANALISIS PEMBAURAN KEBANGSAAN DENGAN MENGGUNAKAN MODEL PENTAHELIX DI KOTA SINGKAWANG - Jannus TH Siahaan; Lalu Budiman (Journal of Innovation Research and Knowledge, 2026)
Indonesia is a multicultural country with an exceptionally high level of ethnic and cultural diversity. While such diversity constitutes a significant national asset, it also carries the potential for social conflict if not managed inclusively and sustainably. Singkawang City in West Kalimantan Province is widely recognized as one of the regions that has successfully maintained national integration and social harmony amid pluralism. This study aims to analyze the process of national integration (pembauran kebangsaan) in Singkawang through the Pentahelix Model, focusing on the social condition of the community, the roles of five key actors (government, academia, business sector, community, and media), and the challenges and opportunities in its implementation. This research employs a qualitative approach with a descriptive-analytical design and a case study strategy. Data were collected through in-depth interviews, participatory observation, document analysis, and media content analysis. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification through triangulation. The findings reveal that Singkawang’s social condition is relatively harmonious, stable, and inclusive. National integration is realized not through assimilation, but through normative pluralism characterized by mutual respect across ethnic and religious identities. This success is supported by historical, territorial, and economic factors functioning as social glue. The Pentahelix Model proves to be relevant in strengthening social integration through multi-stakeholder collaboration. However, the development of a technology-based early warning system is necessary to enhance collaborative conflict prevention mechanisms. This study concludes that sustainable national integration requires contextual and adaptive collaborative governance supported by continuous synergy among Pentahelix actors